The Pastor's Understanding of the Baptist Church in Bandung Area Regarding the Spiritual Growth of Children with Special Needs Based on Matthew 19:13-15: Pemahaman Gembala Sidang Gereja Baptis di Wilayah Bandung Mengenai Pertumbuhan Rohani Anak Berkebutuhan Khusus Berdasarkan Matius 19:13-15 - Christina Galih Sanjaya; Djoko Sukono; Nixon Dixon Siathen (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
Not many people are burdened to educate children with special needs in the Christian faith. The church is a means for spiritual growth and development, only a few churches carry out the ministry of serving children, especially those with special needs for an example teachers are paying less attention to those who has special needs. This research is a qualitative descriptive design research using the interview method as a data collection tool. Participants were pastors of the Baptist church union in the Bandung area totaling 4 people. The study was conducted in four Baptist churches in the Bandung area, West Java. The result of this study conclude that the understanding of Baptist church pastors in Bandung area about the spiritual growth of children with special needs is appropriate. Relating to spiritual growth, which is a process to be Christ-like that is carried out continuously throughout the life and is also very important for children with autism with special guidance either through parents or Sunday school teachers who are involved in every event that helps spiritual growth such as the Bible reading and praying can be followed by children with autism. The policy carried out by the pastor of the Baptist church in Bandung as a tool for the spiritual growth of children with special needs, related to this matter, by time does not yet exist but some churches provide the same service and provide special needs teaching assistance to company teachers in Sunday school classes.